QS8: Analysis of the Whole Transcriptome in Breast Cancer Patients Undergoing Radiotherapy and Breast Reconstruction - Miller, Andrew (Plast Reconstr Surg Glob Open, 2021)
PURPOSE: Breast cancer is the third highest cause of death among all cancers in women. Patients who undergo mastectomy for tumor removal often undergo adjuvant radiation therapy and elect to have breast reconstruction. An adverse side-effect of radiation therapy is radiation-induced fibrosis (RIF), causing thickening and tightening of the tissues on the chest wall and around the reconstructed breast. This can result in pain and/or aesthetically displeasing results. Of the many studies investigating potential mechanisms for RIF production, none to our knowledge, have measured the whole-transcriptome response in local tissues around the reconstructed breast. Thus, we utilized whole-transcriptome sequencing to understand the potential expression pathways for clinical intervention. METHODS: Unilateral breast cancer patients undergoing a bilateral mastectomy with reconstruction were recruited for the current study. A total of 7 patients were recruited for this study. During the initial surgical mastectomy procedure, tissue expanders were placed in the sub-pectoral plane. Patients subsequently underwent unilateral radiation therapy of the affected breast. Approximately three months after completing radiation therapy, the tissue expanders were removed and the final definitive reconstruction performed. At this time, skin, the fibrotic capsule surrounding the expander (capsule) and muscle tissues were collected. From these samples, transcriptome-wide RNAs were extracted, processed, and sequenced. After sequence alignment, transcripts were counted and filtered, requiring at least ten counts per gene to be included for subsequent analyses. Differential expression analyses for each tissue type, between non-radiated and radiated samples, were performed incorporating RIN score, tissue type, and radiation status into the statistical model. Using the Gene Ontology (GO), an enrichment analysis was performed on the significant genes from the differential expression analyses. RESULTS: After applying quality control metrics, 39 samples remained. On average, samples had an alignment of 84.5%, quality scores above 32, and RIN value of 7.5. The total number of significant genes and GO terms identified for the skin, capsule, and muscle was 29, 39, 48 genes; 25, 29, 42 GO terms, respectively. In skin tissue, multiple keratin genes and TCHH were identified, contributing to the GO process: keratinocyte differentiation, cornification, intermediate filament organization, hair follicle morphogenesis. Significant genes in the capsule tissue included collagen genes (COL4A5 and COL6A6), SLC6A13, and CLCA2. CDKN1A and PDGFRA contributing to the significant GO process of positive regulation of fibroblast proliferation. In muscle tissue, significant genes of interest include BAX, TOP2A, MDM2, and CXCL10, which are associated with processes such as DNA damage and response to radiation. CONCLUSION: In the current study, we have identified differentially expressed genes in the skin, fibrotic capsule, and muscular tissue that received radiation therapy. Signs of typical side effects can be observed by the presence of genes involved in DNA damage and fibroblast proliferation GO processes. Additionally, significant genes were identified that are involved in biological processes not previously associated with RIF, such as intermediate filament organization and hair follicle morphogenesis. These results contribute to a deeper understanding of RIF development in breast cancer patients receiving radiation therapy and may advance the potential for improving RIF mitigation.